Providing Ideal Restitution to Rape Victims Based on the Principle of Justice - Rodhi Agung Saputra; Agnes Atia Aurellia; Adinda Bintang Maharani (PT FORMOSA CENDEKIA GLOBAL, 2023)
Problems related to rape cases are still carried out from adolescence to adulthood. This case has a negative impact on the image of the nation, especially for rape victims who can cause material and immaterial losses to victims of criminal acts, so the principle of justice is needed to provide legal certainty for victims of crimes, especially rape victims, to get restitution from the losses of these crimes. The problem that will be discussed in this study is how to provide ideal restitution to rape victims based on the principle of justice. The research method used in this study is a normative research method using a statutory approach and a case approach and will be analyzed using analytical content.